Analisis Karakteristik dan Startifikasi Tanah Menggunakan Data CPT sebagai Dasar Penentuan Kedalaman Pondasi - Yayu Sriwahyuni Hamzah; Ahmad Sirrotun Najwaa (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2024)
Foundations are structural elements that play a crucial role in ensuring the stability and safety of buildings; therefore, understanding soil characteristics and stratification is a critical stage in geotechnical design. This study aims to analyze soil characteristics and stratification using Cone Penetration Test (CPT) data as a basis for determining safe and efficient foundation depth. The research method employed a quantitative–descriptive approach utilizing CPT test data obtained from two test points at the research site in Blitar City, East Java. The analyzed parameters include cone resistance (qc), sleeve friction (fs), and friction ratio (Rf), which were recorded continuously with depth in accordance with ASTM D3441-86. The results indicate that the shallow soil layer up to a depth of approximately 2.0 m is dominated by fine-grained soils with low qc values and high Rf values, making it unsuitable as a foundation bearing layer. The soil layer with the most favorable mechanical characteristics was identified at a depth of approximately 5.5–6.0 m, characterized by high and relatively stable qc values and low Rf values, indicating dense coarse-grained soil. Variations in the depth of hard soil layers between test points suggest lateral variability in subsurface conditions. These findings confirm that CPT data are effective for identifying soil stratification and providing preliminary recommendations for foundation depth in geotechnical planning.